Non-Gaussianity from Particle Production during Inflation - Neil Barnaby (Advances in Astronomy)
In a variety of models the motion of the inflaton may trigger the production of some non-inflaton particles during inflation, for example via parametric resonance or a phase transition. Such models have attracted interest recently for a variety of reasons, including the possibility of slowing the motion of the inflaton on a steep potential. In this review we show that interactions between the produced particles and the inflaton condensate can lead to a qualitatively new mechanism for generating cosmological fluctuations from inflation. We illustrate this effect using a simple prototype model g2(ϕ−ϕ0)2χ2 for the interaction between the inflaton, ϕ, and iso-inflaton, χ. Such interactions are quite natural in a variety of inflation models from supersymmetry and string theory. Using both lattice field theory and analytical calculations, we study the production of χ particles and their subsequent rescatterings off the condensate ϕ(t), which generates bremsstrahlung radiation of light inflaton fluctuations δϕ. This mechanism leads to observable features in the primordial power spectrum. We derive observational constraints on such features and discuss their implications for popular models of inflation. Inflationary particle production also leads to a very novel kind of nongaussian signature which may be observable in future missions.